2021
DOI: 10.1002/nur.22159
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum depression and family function in Chinese women within 1 year after childbirth: A cross‐sectional study

Abstract: Family‐related factors are reported to influence the development of postpartum depression (PPD), but limited studies have considered the role of family function in this condition. This study aimed to describe the proportion of people with probable or suspected PPD and to determine the relationships among PPD, family function, and obstetric factors. A cross‐sectional study was conducted with 630 women who attended six integrated teaching and scientific research communities in Changsha, China. Instruments includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
2
7
0
Order By: Relevance
“…In our study, it was found that low problem solving in family relations and unhealthy communication were important related factors for experiencing PPD symptoms. Studies conducted in China have reported that unhealthy family function has a direct negative relationship with postpartum depression, consistent with our study findings (Guan et al, 2021; Huang et al, 2021). Chen et al (2017) studied the characteristics of family functioning in patients with major depression, and stated that the more dysfunctional a family's communication is, the higher the risk of PPD.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, it was found that low problem solving in family relations and unhealthy communication were important related factors for experiencing PPD symptoms. Studies conducted in China have reported that unhealthy family function has a direct negative relationship with postpartum depression, consistent with our study findings (Guan et al, 2021; Huang et al, 2021). Chen et al (2017) studied the characteristics of family functioning in patients with major depression, and stated that the more dysfunctional a family's communication is, the higher the risk of PPD.…”
Section: Discussionsupporting
confidence: 93%
“…High family functioning can be significant for young mothers' psychological wellbeing, with studies showing that women living in families with high family functioning are less likely to have emotional symptoms and are more likely to have higher levels of self-efficacy in maternal roles. 37–39 Based on this information, it might be beneficial that young mothers count on significant family members to gain positive experiences during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…We consider the following reasons to explain this phenomenon in our study: First, parents / parents-in-law may use their own experiences and parenting methods to influence the new mothers and the babies in China. When the ideas of parenting are different from both parties, it may cause family conflicts, frustrations, and negative emotions to new mothers [ 43 ]. During the COVID period, parents visiting was very limited and even forbidden.…”
Section: Discussionmentioning
confidence: 99%